Translation Quality in Student-Generated Subtitles: A Study on Nwal Hadaki’s TED Talk - Hidayatun, Muthiah; Hartono, Rudi; Wahyuni, Sri; Gazaly, Muragmi (Institut Agama Islam Negeri Kendari, 2025)
The present study explored the use of interlingual subtitling tasks to improve translation quality and student motivation. Using a qualitative descriptive approach with content analysis, 14 English Education students participated in a subtitling activity. Their work was evaluated for accuracy, acceptability, and readability, with multiple raters ensuring reliability. Findings revealed that although most subtitles were generally understandable, issues remained in terms of natural flow, contextual precision, and linguistic appropriateness. This study suggests that incorporating subtitling into translation pedagogy not only diversifies learning activities but also supports the development of key translation competencies. It highlights the value of engaging, real-world tasks in maintaining learner interest and enhancing translation quality.